Nanomorphology and charge generation in bulk heterojunctions based on low-bandgap dithiophene polymers with different bridging atoms - Morana, Mauro; Azimi, Hamed; Dennler, Gilles; Egelhaaf, Hans-Joachim; Scharber, Markus; Forberich, Karen; Hauch, Jens; Gaudiana, Russell; Waller, David; Zhu, Zenghuo; Hingerl, Kurt; Van Bavel, Svetlana S.; et al. (Advanced Functional Materials, 2010)
Carbon bridged (C-PCPDTBT) and silicon-bridged (Si-PCPDTBT) dithiophene donor-acceptor copolymers belong to a promising class of low bandgap materials. Their higher field-effect mobility, as high as 10cm V s in pristine films, and their more balanced charge transport in blends with fullerenes make silicon-bridged materials better candidates for use in photovoltaic devices. Striking morphological changes are observed in polymer:fullerene bulk heterojunctions upon the substitution of the bridging atom. XRD investigation indicates increased π-π stacking in Si-PCPDTBT compared to the carbon-bridged analogue. The fluorescence of this polymer and that of its counterpart C-PCPDTBT indicates that the higher photogeneration achieved in Si-PCPDTBT:fullerene films (with either [C60]PCBM or [C70]PCBM) can be correlated to the inactivation of a charge-transfer complex and to a favorable length of the donor-acceptor phase separation. TEM studies of Si-PCPDTBT:fullerene blended films suggest the formation of an interpenetrating network whose phase distribution is comparable to the one achieved in C-PCPDTBT:fullerene using 1,8-octanedithiol as an additive. In order to achieve a balanced hole and electron transport, Si-PCPDTBT requires a lower fullerene content (between 50 to 60 wt%) than C-PCPDTBT (more than 70 wt%). The Si-PCPDTBT:[C70]PCBM OBH) solar cells deliver power conversion efficiencies of over 5%. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA.